(untitled) (World Bulletin of Public Health, 2023)
Relevance of the topic Parkinson’s disease is one of the important problems of clinical neurology throughout the world and is a chronically developing neurodegenerative pathology of the brain. One of the most observed symptoms of Parkinson’s disease is pain, which significantly reduces the quality of life of patients. Various pain sensations often cause stress in patients, adversely affect adaptation processes and cause depressive changes. On average, 40-80% of patients complain of pain of various nature, duration and localization.